Interface binding and mechanical properties of MXene-epoxy nanocomposites. (26th May 2020) - Sliozberg, Yelena; Andzelm, Jan; Hatter, Christine B.; Anasori, Babak; Gogotsi, Yury; Hall, Asha
Abstract: Thermosetting epoxy polymers exhibit excellent stiffness and strength and are commonly utilized as matrices to make fiber reinforced composites. However, epoxy thermosets are brittle and typically possess a low fracture toughness that restricts their applications. One promising mechanism for improving mechanical properties of epoxy is the integration of micro- and nano-scale fillers. MXenes, a large family of 2D transition-metal carbides, carbonitrides, and nitrides, can be used to produce multifunctional polymer nanocomposites due to their excellent electrical, thermal, and mechanical properties. We employed density functional theory and coarse-grained molecular dynamics simulations to evaluate binding energy and microscopic mechanisms of fracture under uniaxial tension for MXene-epoxy composites. The simulation results were verified by manufacturing Ti3 C2 T x MXene-epoxy composites and studying their structure and fracture surfaces. MXene-epoxy binding energies are largely unaffected by MXene type (Ti2 CT x or Ti3 C2 T x ). Binding between Ti3 C2 T x and epoxy becomes stronger with less hydrogen coverage of Ti3 C2 T x surface due to increase in favorable electrostatic interactions. The Young's modulus of MXene-epoxy composites is greater compared to the neat epoxy which originates from stress transfer between the matrix and the nanofiller, the modulus linearly increases with the filler loading up to 1 vol %. At higher filler contents, the increase of the modulus is reduced due to filler aggregation. Void formation was detected near edges of the particles in MXene-epoxy composites under deformation from both experimental and simulation studies of the fracture surfaces. From these observations, we expect the MXene fillers to improve epoxy toughness and enhance its mechanical performance.